Under the Shadow of the Rising Sun Japan and the Jews during the Holocaust Era - Medzini, Meron (Jewish Identities in Post-Modern Society, 2016)
Even before Japan joined Nazi Germany in the Axis Alliance, its leaders clarified to the Nazi regime that the attitude of the Japanese government and people to the Jews was totally different than that of the official German position and that it had no intention of taking measures against the Jews that could be seen as racially motivated. During World War II some 40,000 Jews found themselves under Japanese occupation in Manchuria, China and countries of South East Asia. Virtually all of them survived the war, unlike their brethren in Europe. This book traces the evolution of Japan's policy towards the Jews from the beginning of the 20th century, the existence of anti-Semitism in Japan, and why Japan ignored repeated Nazi demands to become involved in the "final solution."